2014
DOI: 10.14737/journal.aavs/2014/2.4.226.232
|View full text |Cite
|
Sign up to set email alerts
|

Sexing of Spermatozoa in Farm Animals: a Mini Review

Abstract: Livestock farmers always have a wish for producing young ones of desired sex. Among the several techniques available, use of sexed semen for artificial insemination is recognized as more pragmatic and easy way to pre -select the sex of the offspring. Selective use of sexed semen in breeding will not only increase the genetic progress from the daughter -dam path but would also help in producing good male germplasm from elite bulls for future breeding. Several attempts have been made, elsewhere in the globe, to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 52 publications
(65 reference statements)
0
8
0
2
Order By: Relevance
“…In stallion spermatozoa, the DNA fragmentation index post-sorting were ∼10% higher than pre-sorting, which may be due to oxidative DNA damage (67). Factors such as high pressure and speed, during sorting, dye-induced defects, electrical deviation, changes in pH and osmolarity, etc might lead to changes to the sperm plasma membrane, trigger pre capacitation-like changes, cause protamine decondensation and alter sperm DNA quality (68).…”
Section: Sex Sorting Of Spermatozoamentioning
confidence: 99%
“…In stallion spermatozoa, the DNA fragmentation index post-sorting were ∼10% higher than pre-sorting, which may be due to oxidative DNA damage (67). Factors such as high pressure and speed, during sorting, dye-induced defects, electrical deviation, changes in pH and osmolarity, etc might lead to changes to the sperm plasma membrane, trigger pre capacitation-like changes, cause protamine decondensation and alter sperm DNA quality (68).…”
Section: Sex Sorting Of Spermatozoamentioning
confidence: 99%
“…al., 2018). Spermatozoa yang mengandung kromosom Y dan X memiliki beberapa perbedaan seperti, ukuran spermatozoa Y lebih kecil, spermatozoa Y mengandung DNA yang lebih sedikit sehingga pergerakannya cepat dan spermatozoa Y mengandung H-Y antigen (Boro, et. al., 2016).…”
Section: Pendahuluanunclassified
“…This can be achieved by effective sorting of X (female) or Y (male) chromosomebearing spermatozoa in semen. Amongst various experimental techniques for separation of X and Y sperm, (Prakash et al, 2014), flow cytometry method which is based on DNA differences poses to be a major breakthrough in reproduction technology Blondin et al (2009). This technique was developed by Johnson et al1989, at the USDA Beltsville Agricultural Research Center and is the only method validated so far for sex selection before birth (Graaf et al, 2009;Prakash et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Amongst various experimental techniques for separation of X and Y sperm, (Prakash et al, 2014), flow cytometry method which is based on DNA differences poses to be a major breakthrough in reproduction technology Blondin et al (2009). This technique was developed by Johnson et al1989, at the USDA Beltsville Agricultural Research Center and is the only method validated so far for sex selection before birth (Graaf et al, 2009;Prakash et al, 2014). But, in addition to being a costly technique, many studies have reported that sperms sexed using this technique possess reduced fertility (Seidel et al1999;Sartori et al 2004;Seidel and Schenk, 2008).…”
Section: Introductionmentioning
confidence: 99%